Successional occurrence of two papulosquamous disorders in HIV positive patient: a rare case report - Deshmukh, Nitika Sanjay; Chavan, Ravindranath Brahmadeo; Gosavi, Anil Prakash; Kachare, Supriya Ashok (International Journal of Research in Dermatology, 2021)
Presentation of two papulosquamous disorders in a same individual is rare condition till date. Independently, psoriasis and Lichen planus (LP) are common inflammatory skin conditions affecting around 2-3% and 1% of HIV (Human immune deficiency) positive population respectively. As reviewed in the literature, psoriasis may be independently associated with other autoimmune conditions like vitiligo, alopecia areata, lichen planus, and discoid lupus erythematosus. In this article, we presented a case report of a HIV seropositive patient who suffered from psoriasis and lichen planus. The coexistence of psoriasis and lichen planus in one individual is rare and underreported in literature. Psoriasis or lichen planus may be the presenting feature of HIV infection and tends to be more severe, to have atypical presentations. Psoriasis and lichen planus can be coexistent or successionally appear one after other in one individual though rare presentation. High index of suspicion is always required while dealing with papulosquamous lesions in PLHIV.